The territories of the People's Republic of China - Boland-Crewe, Tara; Lea, David, 1972- (Europa, 2002)
Provides up-to-date and impartial information that helps give an understanding of the regional dimension of the country as well place it in economic, political and historical contexts.
Includes indexes.
Keywords: China -- Territories and possessions.; HISTORY.; Chinese territories and possessions